Exploring the impact of directionality on disfluencies in simultaneous interpreting - Gierszal, Sylwia; Łyda, Andrzej (East European Journal of Psycholinguistics, 2023)
This paper focusses on the concept of directionality in interpreting. The main aim of this study is to investigate four types of disfluencies in simultaneous interpreting performed by students and the impact of pausal phenomenon on directionality. Disfluencies being inseparable element of speech are the factor that has a substantial influence on interpreting process including directionality. The participants in this study were 12 advanced interpreting students who interpreted simultaneously two texts from A language into B language and two texts from B language into A language. Their outputs were later analysed taking into consideration four types of disfluencies and verified how they influence directionality. This study offers some insights into occurrences of disfluencies. Research findings show that students display tendency to produce more disfluencies while interpreting into A language. In addition, the obtained results highlight the necessity to focus not only on fluency but also on disfluencies while interpreting training to improve quality in simultaneous interpreting in both directions. Disclosure Statement No potential conflict of interest was reported by the authors. * Corresponding author: Sylwia Gierszal, 0000-0002-8068-6211 sylwia.gierszal@us.edu.pl